2016
DOI: 10.1186/s40536-016-0021-7
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of Swedish and Norwegian students’ overall and digital reading performance with a focus on equity aspects of education

Abstract: Background: Influence of external factors in general, and socioeconomic background factors in particular, on traditional reading performance has been extensively researched and debated. While traditional reading is well investigated in this respect, there is a lack of studies on equity aspects related to digital reading achievement, in spite of the fact that time spent on reading from digital devices such as computers, tablets, and smart phones without doubt is increasing all over the world. In the hope of con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
(44 reference statements)
2
10
0
Order By: Relevance
“…Indeed, the impact of SES weakens in online reading and digital competence compared with traditional reading proficiency studies (Frønes & Narvhus, 2011;Olsen et al, 2015;Rasmusson, 2016), and our findings confirm this. However, why does reading online texts in new formats place students in a more equitable learning situation?…”
Section: Equitable New Reading Challenges?supporting
confidence: 79%
See 1 more Smart Citation
“…Indeed, the impact of SES weakens in online reading and digital competence compared with traditional reading proficiency studies (Frønes & Narvhus, 2011;Olsen et al, 2015;Rasmusson, 2016), and our findings confirm this. However, why does reading online texts in new formats place students in a more equitable learning situation?…”
Section: Equitable New Reading Challenges?supporting
confidence: 79%
“…For our purposes, dynamic texts refer to interactive hypertext where the readers choose their own reading path, here including texts designed for the Internet and social media. Studies have shown that gender and home background seem to have less of an effect on students' performance in Nordic countries, among others, when reading digital texts compared with reading traditional texts (Fraillon, Ainley, Schulz, Friedman, & Gebhardt, 2014;Frønes & Narvhus, 2011;Olsen, Hatlevik, & Loi, 2015;Rasmusson, 2016). However, none of these studies have investigated whether the weakened effect on performance is covaried with the digital format, the text types or the reading tasks.…”
mentioning
confidence: 99%
“…This observation was confirmed by Hanchane, Benbiga, and Idir [21], Linn, Hyde, and Else-Quest (2010), Ian, Armstrong, and Rounds (2009), Fuchs and Wößmann [19], Murphy [17], and Lamon, Fennema, and Hyde (1990). A meta-analysis by Su, Armstrong, and Rounds [18] explained this difference by noting that men prefer to work with things and tend to study fields such as science, mathematics, and engineering, while women prefer to work with people, and thus develop interests related to artistic and social activities.…”
Section: Student Characteristics and School Performancesupporting
confidence: 53%
“…These studies have suggested that girls outperform boys in reading, while the reverse is true in quantitative subjects. Adopting an international perspective, Rasmusson [19] examined gender differences in the variability of student performance and found that boys performed better in mathematics and science subjects.…”
Section: Student Characteristics and School Performancementioning
confidence: 99%
“…Wu et al studied the relationship between principals’ leadership and student achievement using PISA 2015 United States data [ 12 ]. In [ 13 ], the study aimed at investigating to what degree external factors, such as cultural and economic capital, parental pressure, and school choice, are related to 15-year-old students’ achievement in digital reading and in overall reading on both the student level and the school level in Norway and Sweden, using PISA data from the two countries.…”
Section: Introductionmentioning
confidence: 99%